Preclinical Pharmacokinetics and In Vitro Metabolism of Asunaprevir (BMS‐650032), a Potent Hepatitis C Virus NS3 Protease Inhibitor. Issue 9 (28th January 2015) - Mosure, Kathleen W.; Knipe, Jay O.; Browning, Marc; Arora, Vinod; Shu, Yue‐Zhong; Phillip, Thomas; Mcphee, Fiona; Scola, Paul; Balakrishnan, Anand; Soars, Matthew G.; Santone, Kenneth; Sinz, Michael; et al.
<x xml:space="preserve">Abstract</x> Asunaprevir (ASV; BMS‐650032), a low nanomolar inhibitor of the hepatitis C virus (HCV) NS3 protease, is currently under development, in combination with other direct‐acting antiviral (DAA) agents for the treatment of chronic HCV infection. Extensive nonclinical and pharmacokinetic studies have been conducted to characterize the ADME properties of ASV. ASV has a moderate to high clearance in preclinical species. In vitro reaction phenotyping studies demonstrated that the oxidative metabolism of ASV is primarily mediated via CYP3A4; however, studies in bile‐duct cannulated rats and dogs suggest that biliary elimination may contribute to overall ASV clearance. ASV is shown to have hepatotropic disposition in all preclinical species tested (liver to plasma ratios >40). The translation of in vitro replicon potency to clinical viral load decline for a previous lead BMS‐605339 was leveraged to predict a human dose of 2 mg BID for ASV. Clinical drug–drug interaction (DDI) studies have shown that at therapeutically relevant concentrations of ASV the potential for a DDI is minimal. The need for an interferon free treatment combined with ASV's initial clinical trial data support development of ASV as part of a fixed dose combination for the treatment of patients chronically infected with HCV genotype 1. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:2813–2823, 2015